Incidence of solid cancer in patients with follicular lymphoma. (2nd November 2019) - Sorigue, Marc; Prusila, Roosa E.I.; Jauhiainen, Jyrki; Mercadal, Santiago; Postila, Aleksi; Salmi, Petteri; Tanhua, Taru; Tikkanen, Susanna; Kakko, Sakari; Kuitunen, Hanne; Pollari, Marjukka; Nystrand, Ilja; et al.
Abstract: Introduction: Patients with follicular lymphoma (FL) have classically had a higher risk of solid cancers than the general population, but there is little data available in patients diagnosed and treated with modern day regimens. Material and methods: We conducted a retrospective multicenter study assessing the cumulative incidence of solid cancers other than nonmelanoma skin cancer in patients with FL between 1997 and 2016 and determined the standardized incidence ratio (SIR) to compare the incidence of solid cancers with that of the general population Results: Among 1002 FL patients with 7 years of median follow-up, we found 74 solid cancers (most common breast [ n  = 19], lung and colon [ n  = 9 each]). The cumulative incidence was 3.8% at 5 years (95%CI 2.6–5.2) from the time of diagnosis and 4.4% at 5 years (95%CI 3.1–5.9%) from the time of front-line treatment. Although a comparison of all front-line strategies did not reveal differences in the risk of solid cancers, patients treated with anthracycline-based regimens appeared to have a lower incidence than those treated with bendamustine-based strategies (2.8% vs. 6.9%). However, patients receiving the former regimen were younger than the latter. On multivariable analysis, older age was correlated with the incidence of solid cancer and bendamustine-based treatment was of borderline significance. SIR for any solid cancer was 1.22 (95%CI 0.91–1.64), indicating no increased risk of solid cancer in patients with FL over that of the general population. However, on subgroup analyses, female patients treated with bendamustine-based strategies appeared to have a greater risk (SIR 3.85 [95%CI 1.45–10.27]) Discussion: The incidence of solid cancer in this cohort of patients with FL was low and not greater than in the general population. However, the risk may be greater in female patients treated with bendamustine.